2022
DOI: 10.3390/ma15103533
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Wear and Corrosion Performance of Mg-Sn-Ti Alloys Produced by Casting and Extrusion

Abstract: The aim of the present study is to investigate the role of Ti on corrosion and the wear properties of Mg-5Sn-xTi (x = 0, 0.15, 0.75, 1.5 wt.%) alloys. The samples were fabricated by conventional casting followed by hot extrusion, and the studies were examined by means of a pin-on-disc tribometer at various loads of 6, 10, and 20 N with constant sliding velocities of 0.04 m/s at ambient temperature. The corrosion performance, using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Mg alloys are the lightest metallic structural materials with superior properties, such as excellent castability, good damping capacity, and high specific strength, making them ideal light-weight materials for applications in many industrial fields including automobiles and rail traffic [ 1 , 2 , 3 , 4 , 5 ]. It has been reported that every weight reduction of 100 Kg of a vehicle reduces the fuel consumption by 0.3–0.4 L/100 km [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloys are the lightest metallic structural materials with superior properties, such as excellent castability, good damping capacity, and high specific strength, making them ideal light-weight materials for applications in many industrial fields including automobiles and rail traffic [ 1 , 2 , 3 , 4 , 5 ]. It has been reported that every weight reduction of 100 Kg of a vehicle reduces the fuel consumption by 0.3–0.4 L/100 km [ 6 ].…”
Section: Introductionmentioning
confidence: 99%